The tyrosine kinase Yes1 is a druggable host factor of HEV - Haase, Jil Alexandra; Baheerathan, Abarna; Zhang, Xin; Fu, Rebecca Menhua; Nocke, Maximilian K.; Decker, Charlotte Caroline; Dao Thi, Viet Loan; Todt, Daniel; Neyts, Johan; Kaptein, Suzanne J. F.; Steinmann, Eike; Kinast, Volker (Hepatology communications, 2024)
Background: HEV is a positive-sense, single-stranded RNA virus of the Hepeviridae family. Although HEV accounts for more than 3 million symptomatic cases of viral hepatitis per year, specific anti-HEV therapy and knowledge about HEV pathogenesis are scarce. Methods: To gain a deeper understanding of the HEV infectious cycle and guide the development of novel antiviral strategies, we here used an RNAi mini screen targeting a selection of kinases, including mitogen-activated protein kinases, receptor tyrosine kinases, and Src-family kinases. Further, we used state-of-the-art HEV infection models, including primary human hepatocytes and athymic nude rats. Results: Upon knockdown of the Src-family kinase Yes1, a significant reduction of HEV susceptibility could be observed, suggesting an important role of Yes1 in the HEV infectious cycle. Selective inhibition of Yes1 kinase activity resulted in significant inhibition of HEV infection in hepatoma cells and primary human hepatocytes, as well as in a rat HEV in vivo model system. Subsequent analysis of Y1KI during the HEV infectious life cycle indicated a role of Yes1 kinase activity in the early onset of HEV infection. Conclusions: We identified the dependence of HEV on Yes1 signaling, which may contribute to the so far scarce knowledge of HEV’s pathogenesis in the future. Moreover, we provide Y1KI as a novel antiviral drug candidate specifically targeting an HEV host factor.